BARRIERS FACED BY THE PRODUCERS OF AYURVEDIC PRODUCTS IN KERALA - Ramalekshmi. S and D. ELANGOVAN (International Journal of Advanced Research, 2015)
Ayurveda has been a lively system of health with an unbroken practice since 3000 years. Ayurveda is a wholistic system of medicine from India that aims to provide guidance regarding food and lifestyle so that healthy people can stay healthy and folks with health challenges can improve their health. It is based on the belief that health and wellness depend on a delicate balance between the mind, body, and spirit. The primary focus of Ayurvedic medicine is to promote good health, rather than fight disease. In spite of growth and prospects progressing for Ayurvedic products, there are lot barriers for the produces. Although, Ayurveda are considered to have early identity, its growth and success in the universal scenario is still in development stages. Hence, the study is an attempt to find the barriers in Ayurvedic Products which has some medicinal values in any form of its produce. This study is conducted mainly in Kerala, considering the high potential market among the mass, who ever have strong belief in Ayurveda. The researcher attempted to find the types of barriers faced by manufacturers of Ayurvedic Products.